Islamic Da'wa, Urban Society And Plurality (Case Study In Mataram -West Nusa Tenggara) - Nazar Naamy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This article tries to elaborate Islamic da'wa activism in the midst of urban community in Mataram city. By emphasizing the pluralism-based da'wah paradigm, this study wants to ethnographically explore how da'wah patterns develop in the midst of urban Muslims and religious heterogeneity in the city of Mataram, Lombok. There are two main focuses of this research: First, what are the factors that encourage and inhibit da'wah in urban and heterogeneous communities in Mataram City. Second, how da'wa strategy  developed in the plural city of Mataram. Through descriptive-exploratory methods and ethnographic approaches, this study shows: First, the preachers in Mataram City still use conventional da'wah strategies, even though they already have an awareness of plurality and heterogeneity of Mataram City. Second, the pattern of da'wah in the city of Mataram from has undergone a shift in the reorientation of da'wah, namely starting to appreciate the spirit of diversity (pluralism) at the level of religious diversity and religious beliefs. This shift in da'wah orientation is due to the strengthening of the dakawah pluralism paradigm in Mataram City which emphasizes the importance of dialogue between religious faith groups and interfaith groups.